IMPLEMENTASI KURIKULUM 2013 TINGKAT PENDIDIKAN DASAR MADRASAH IBTIDAIYAH NEGERI (MIN) DI KABUPATEN ACEH SELATAN (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2021)
Research was carried out on the subject of "Implementation of the 2013 curriculum for the elementary level of the State Islamic Middle School (MIN) in South Aceh Regency". This research was conducted at MIN in the South Aceh Regency and included up to 27 MINs. This research was conducted using a triangulation of research method, blending or mixing a qualitative and quantitative. The selection of the research sample was done by randomsampling. The stages of the research include the distribution of research instruments in the form of questionnaires to be filled out by the teacher, subsequent observations and interviewswith the headmaster and the teachers of the MIN. The results of the questionnaire on the success rate of curriculum implementation in 2013 showed the "medium" category with a percentage of 69.50%, while for the "high" and "low" categories, each showed a figure of 6.78%. The results of interviews with school principals and MIN teachers revealed that the implementation of the 2013 curriculum in MIN in South Aceh Regency had been applied for 3 years specifically for Islamic Religious Education (PAI) subjects. The obstacles MIN teachers face in the South Aceh Regency area are the teachers' lack of understanding of theimplementation of the teaching and learning process, the design of learning devices, limited facilities and supporting infrastructure, IT mastery and the use of 2013 curriculum evaluation applications.